HUBUNGAN KOMPETENSI KEPRIBADIAN GURU DENGAN DISIPLIN SISWA KELAS VI - Siti Animah; Sholeh Hidayat Hidayat; Lukman Nulhakim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The background of this research is the low awareness of discipline. This study aims to determine the correlation of teacher personality competence with student discipline and how much the correlation between teacher competency and student discipline. The research method used is correlational. This research was conducted in class VI SDN Majalaya with a sample of 30 students. Data collection techniques are Likert scale questionnaires that have been tested for validity and reliability. Based on the results of the correlation analysis test obtained a correlation coefficient of 0.61 with a significance of 0.000. The significance value obtained is 0.000. 0.000 <0.05 thus there is a correlation between the teacher's personal competence and student discipline.